Evaluation of Role of Some Adipokines and Anti-Mullerian Hormone in Women with Polycystic Ovary Syndrome in Nineveh Governorate – Iraq - Rajaa Al-Taii; Muna Hussein Jankeer (Acta Scientiarum. Animal Sciences, 2025)
Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders among women of reproductive age and one of the most important causes of poor fertility, This syndrome is accompanied by metabolic dysfunction and poor fertility. This study aimed to evaluate the role of some adipokines (chemerin and visfatin) among the causes of the disease and anti-Müllerian hormone (AMH) as a basic indicator of this syndrome, in the serum of 100 female patients, it included single and married women who do not have children (primary infertility) and women who are married but have children (secondary infertility), their ages ranged between (15-45) years, from visits to both Al-Batoul and Al-Khansaa Teaching Hospital for Obstetrics and Gynecology in Nineveh Governorate, who was diagnosed with the syndrome by obstetricians, gynecologists and poor fertility doctors, as well as 50 healthy females (single and married women) of the same ages who were considered as a control group. The results of the study showed a significant increase in the probability level (p ≤ 0.01) in the level of chemerin, visfatin, and anti-Müllerian hormone (AMH). The 26% of chemerin in the serum of the women with PCOS reached single women, 26% for single women, 40% for married women, 46% for married women with primary infertility and for married women with secondary infertility was 32% compared to control, and the rate of increase in visfatin in affected women was 22% for single women, 26% for married women, 31% for married women with primary infertility and for married women with secondary infertility 21% compared to control, while the rate of increase in anti-Müllerian hormone in affected women reached 128% for single women,108% for married women, 103% for married women with primary infertility and 163% for married women with secondary infertility compared to control. We conclude from this study that chemerin, visfatin, and AMH can be used as a biomarker for early detection of PCOS and clinical signs such as poor fertility and hyperandrogenism in women with polycystic ovary syndrome.